Evaluation of Two Methods of Temperature Measurement in Children: Mercury-in-glass Thermometer (MIGT) versus Non-Touch Infrared Thermometer (NTIT) - Yetunde Olasinde; Moninuola Ernest; Gbenga Popoola; Ernest Kolade (New Horizons in Medicine and Medical Research Vol. 8, 2022)
Background: Getting an accurate temperature measurement is a critical step in evaluating health or disease especially in children, particularly those with fever and the immuno- compromised subjects. Inaccurate temperature measurement may lead to improper diagnosis, wrong treatment or inappropriate intervention. Also some countries have raised concerns over the continuous use of Mercury-in-glass thermometer because its disposal after use may contaminate the soil and water and finally get into human food or drink and so gradual shift to other methods of temperature measurement is advocated. Several methods of temperature measurements exist and comparing these gives room for choosing a near ideal method in terms of speed, safety and accuracy. Aim: This study therefore, aimed at comparing the forehead non touch infra-red thermometer with the axillary mercury-in-glass method of temperature measurement in the Paediatric age-group. This would help determine the liability of accepting one over the other. Methods: Study was given ethical approval as part of a larger study. Four hundred and thirty seven children aged 1 to 24 months were studied at the well-baby/ immunization clinic of the University of Ilorin Teaching Hospital over a 6-months period. Both Non-Touch Infrared and the regular Mercury-in-Glass Thermometers were used to take the body temperatures. Data were analysed with SPSS version 21. Pearson correlation was used to determine the relationship between the two methods of temperature measurements, while Bland-Altman method was used to test for level of agreement between them. Results: The mean age and SD was 5.81 ± 4.04months. Pearson correlation showed a positive correlation between the Axillary Mercury-in-Glass and Forehead Non-Touch Infra-red thermometry readings (r=0.281, p<0.001). Also, Bland-Altman method revealed a good agreement between both methods of thermometry as 96% of the readings were within the limits of agreement. Mean difference was 0.09 (95% confidence interval 0.05 - 0.13)°C. Conclusion: Axillary Mercury-in-Glass thermometer and Forehead Non touch Infra-red thermometers have a good agreement and can be used interchangeably.